Laparoscopic Treatment for Esophageal Achalasia and Gastro-Esophago-reflex Disease Using Radius Surgical System - Hirano, Yasumitsu (Springer India, 2012)
Radius surgical system (RSS) is a manual manipulator to enhance the surgeon’s dexterity and ergonomy achieving more degrees of freedom, and it enables us easy to perform intracorporeal suturing in laparoscopic surgery. We successfully performed laparoscopic treatment including intracorporeal suturing in cases of esophageal achalasia and gastroesophageal reflux disease using RSS. RSS may facilitate of intracorporeal suturing and knotting in complex laparoscopic procedures.